Control of hippocampal synaptic transmission and plasticity by wakefulnessdependent elevation of astrocyte-derived adenosine. - Schmitt, Lukas. (2017)
Abstract: Sleep is a highly conserved behavior which is critically important to the function of the nervous system and in particular to consolidation of declarative memory. Recent evidence has suggested that astrocytes, the major glial support cell within the brain, play a key role in maintaining sleep homeostasis by governing the level of adenosine which acts in extracellular space to regulate synaptic transmission. In addition, adenosine signaling by these cells has been implicated in the regulation of hippocampal dependent memory, suggesting that they play a previously unrecognized role in information processing within this brain area. Although it is increasingly evident that astrocytes can listen and respond to neurotransmission through calcium dependent exocytotic release, the mechanism by which they respond to wakefulness to affect synaptic transmission remains poorly understood. In this dissertation, I present the results of my investigations into the role of astrocyte-derived adenosine in wakefulness-dependent changes to synaptic transmission and neuroplasticity within the hippocampus. Using a variety of electrophysiological means combined with molecular genetic disruption of astrocytic exocytosis and Inositol tri-Phosphate (IP3) signaling in these cells, I demonstrate for the first time that wakefulness can regulate the level of astrocyte-derived adenosine acting in the hippocampus. I show that acute loss of sleep leads to an increase in signaling by this transmitter, while extended sleep loss produces an allostatic adjustment to reduce the level of adenosine, probably through reduced release, thereby compensating for the effects of chronic sleep disruption. Finally, I show that the mechanism by which astrocytes control extracellular adenosine depends on IP3 calcium mobilization in these cells and that over short time scales astrocyte-derived adenosine can both inhibit synaptic release of glutamate and enhance synaptic plasticity by increasing NMDA receptor mediated responses. Because of the critical importance of sleep in maintaining the health of the nervous system and the comorbidity of sleep pathologies in various neurological and psychiatric disorders, these results hold important implications for understanding the role of both astrocytes and adenosine signaling in health and disease.; Thesis (Ph.D.)--Tufts University, 2014.; Submitted to the Dept. of Neuroscience.; Advisor: Philip Haydon.; Committee: F. Jackson, Michelle Jacob, and Kathleen Dunlap.; Keyword: Neurosciences.